Iridium models of rhodium Intermediates in hydroformylation catalysis: isolation and molecular structures of fluxional ae and ee isomers - Abkai, Golnar; Schmidt, Sebastian; Rosendahl, Tobias; Rominger, Frank; Hofmann, Peter (Organometallics, 2014)
We report the synthesis and single-crystal molecular structures of two stereoisomers of trigonal-bipyramidal hydrido dicarbonyl Ir complexes [(L2)Ir(H)(CO)2] with ae (axial-equatorial) and ee (equatorial-equatorial) ligand P coordination and fluxional behavior in solution. L2 is a new chelating bisphosphite with unprecedented high selectivity in Rh-catalyzed bis-hydroformylation of butadiene to adipic aldehyde. These Ir analogues are ideal stabilized structural models for nonseparable ae and ee Rh-hydroformylation resting state isomers [(L2)Rh(H)(CO)2]. With Ir, both stereoisomers with the same ligand could be characterized independently for the first time.